Kelapa Application: Local Culture-Based Learning Media for Character Strengthening of Pancasila Student Profiles - Ni Made Diah Ariusnita; Gede Wira Bayu (Universitas Pendidikan Ganesha, 2023)
The decline in the Pancasila character values of elementary school students and the less optimal use of local Indonesian culture in learning activities. This study aims to produce application learning media based on local culture to strengthen the character profile of Pancasila students in fourth-grade elementary school students. This development research uses the ADDIE development model. The subjects in this study were two subject matter experts, two learning design experts, two learning media experts, a practitioner, and students divided into three individual test persons and nine small group test persons. Data collection techniques are descriptive qualitative analysis and quantitative descriptive analysis. The results showed that the application learning media developed was declared valid based on the expert review of the subject matter score of 98.33%, the learning design expert's 98.75%, and the expert review of the learning media 95%. As for the level of practicality of the media based on the results of practitioners' responses of 99% (very practical category), student responses in the individual test obtained a score of 100% (very practical category). The results of student responses in the small group test obtained a score of 98.33% (the category very practical). It was concluded that local culture-based application learning media is feasible and practical for the learning process.